==> YES, main.fstb terminates. max_dim = 2 +-----------------------------------------------------------------------------+ | Ranking Function | +-----------------------------------------------------------------------------+ state evalwisestart: 4 state evalwiseentryin: 3 state evalwisereturnin: 1 state evalwisebb6in: 2 (((-3*A)+(-3*B))+(6*A__o))+(6*B__o) state evalwisebb3in: 2 (((-1+(-3*A))+(-3*B))+(6*A__o))+(6*B__o) state evalwisebb4in: 2 (((-2+(-3*A))+(-3*B))+(6*A__o))+(6*B__o) state evalwisebb5in: 2 (((-2+(-3*A))+(-3*B))+(6*A__o))+(6*B__o) state evalwisestop: 0 state ____evalwisestart: 5 +-----------------------------------------------------------------------------+ | Worst Case Execution Time | +-----------------------------------------------------------------------------+ /--- / | A__o'+(-1*B__o') >= 0 | -2+B__o' >= 0 | 1 >= 0 \ (((((((1+1)+1)+((1+B__o')+A__o'))+((-2+B__o')+A__o'))+(-3+(2*B__o')))+((-2+B__o')+A__o'))+1)+1 / | -3+(2*A__o') >= 0 | (-1*A__o')+B__o' >= 0 | -2+B__o' >= 0 | (1+A__o')+(-1*B__o') >= 0 \ (((((((1+1)+1)+((1+B__o')+A__o'))+((-2+B__o')+A__o'))+(-3+(2*B__o')))+(-2+(2*A__o')))+1)+1 / | 1+(-1*B__o') >= 0 | (-3+A__o')+B__o' >= 0 | B__o' >= 0 \ ((((((1+1)+1)+((1+B__o')+A__o'))+((-2+B__o')+A__o'))+((-2+B__o')+A__o'))+1)+1 / | -3+(2*A__o') >= 0 | (-1+(-1*A__o'))+B__o' >= 0 | 1 >= 0 \ (((((((1+1)+1)+((1+B__o')+A__o'))+((-2+B__o')+A__o'))+((-2+B__o')+A__o'))+(-2+(2*A__o')))+1)+1 / | -1+A__o' = 0 | -2+B__o' = 0 | 1 >= 0 \ ((((((1+1)+1)+((1+B__o')+A__o'))+((-2+B__o')+A__o'))+(-3+(2*B__o')))+1)+1 / | A__o' >= 0 | (-3+A__o')+B__o' >= 0 | 2+(-2*A__o') >= 0 \ ((((((1+1)+1)+((1+B__o')+A__o'))+((-2+B__o')+A__o'))+((-2+B__o')+A__o'))+1)+1 / | A__o' >= 0 | (-3+A__o')+B__o' >= 0 | (-2+(-1*A__o'))+B__o' >= 0 | 2+(-2*A__o') >= 0 \ ((((((1+1)+1)+((1+B__o')+A__o'))+((-2+B__o')+A__o'))+((-2+B__o')+A__o'))+1)+1 / | A__o' >= 0 | B__o' >= 0 | 1+(-1*B__o') >= 0 | 2+(-2*A__o') >= 0 \ ((((1+1)+1)+((1+B__o')+A__o'))+1)+1 / | B__o' >= 0 | A__o'+(-1*B__o') >= 0 | (2+(-1*A__o'))+(-1*B__o') >= 0 \ ((((1+1)+1)+((1+B__o')+A__o'))+1)+1 / | A__o' = 0 | -2+B__o' = 0 | 1 >= 0 \ ((((1+1)+1)+((1+B__o')+A__o'))+1)+1 \---